Taste-shaping-natures: making novel miso with charismatic microbes and new Nordic fermenters in Copenhagen - Evans, J; Lorimer, J (University of Chicago Press, 2021)
Taste shapes evolution, microbes make tasty food, and humans and microbes have been shaping each other for a long while. Yet anthropological accounts of evolution and domestication have given little consideration to taste, microbes, or fermentation. In this paper we develop the concept of “taste-shaping-natures”—natures shaping and shaped by taste—to highlight these multispecies interactions, based on practices of translated fermentation in the New Nordic Cuisine. Here, chefs combine Japanese microbes and fermentation techniques with Scandinavian substrates to create new products and flavors. Focusing on novel misos made with the kōji fungus (Aspergillus oryzae), we illustrate how chefs sense their microbes through smell and taste, and identify the sources of kōji’s exceptional microbial charisma. We situate the rise of kōji’s allure in the context of New Nordic Cuisine, framed as a high-end response to anxieties about globalization and subsequent nationalisms, a reworking of the scientism of molecular gastronomy, and a postpastoral mobilization of different natures for the reconstruction of regional identity. The analysis traces the natural history of kōji’s taste-shaping powers through the biogeographical, ecological, and evolutionary consequences of New Nordic fermentation experiments. The conclusion reflects on how this nascent microbiology of desire revises prevalent understandings of domestication.